Pengaruh Kualitas Pelayanan, Pengetahuan Perpajakan dan Penerapan Sistem E-Filling Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Nuriza, Nuriza; Fielnanda, Refky; Sissah, Sissah (Prodi Akuntansi Syariah UIN Sulthan Thaha Saifuddin Jambi, 2022)
Tax compliance is a requirement to fulfill all WPOP obligations towards taxation and exercise their taxation rights. The growth in the number of WPOPs at the Kuala Tungkal KPP Pratama throughout the 2017-2019 period continues to increase greatly each year, but the percentage of taxpayer compliance is still up and down and inconsistently rising. It can be concluded that not all registered WPOPs can effectively fulfill their tax obligations. This research was conducted to determine the effect of service quality, tax knowledge and the implementation of E-Filling on WPOP compliance. This research uses illustrations of 100 WPOPs through questionnaires distributed and interviewed and uses convenience sampling technique for sampling. The data were analyzed using the Multiple Linear Regression Analysis method with the SPSS 22 supporting program. The F test results show that independent variables such as service quality, knowledge of taxation, and the implementation of E-Filling have a simultaneous effect on WPOP compliance. From the results of the t test of the independent variables, there is a partial effect on WPOP compliance. From the results of the adjustment of the coefficient of determination Rsquare (R2) of 0.164 or 16.4% for wpop compliance, this is 83.6 influenced by the independent variable and the remaining% is influenced by other factors not only from the independent variables in this research.